What Makes a Good Quantitative Linguistics Textbook?. Issue 1 (2nd January 2021) - Ouyang, Jinghui; Jiang, Jingyang
ABSTRACT: Quantitative linguistics (QL) is a discipline whose research goal is to explore the language patterns and linguistic laws using quantitative methods. But the word 'quantitative' poses great challenges to many language researchers who have love-hate feelings of QL. To this end, we need a good introductory textbook intended for beginners. But there have been few textbooks in a strict sense until two textbooks of QL were published in 2017: Quantitative Linguistics, an Invitation, and An Introduction to Quantitative Linguistics . In view of the nature of QL, we hold that a good QL textbook should meet the five principles: (1) scientificity, (2) authentic materials, (3) practicality, (4) transparency and (5) transference of knowledge. Based on the five principles, we introduced and analyzed these two textbooks. We came to the conclusion that both books can be regarded as good textbooks for beginners and researchers of QL. In the future, more high-quality QL textbooks are expected, written in different languages and with exercises to boost the discipline development of QL.